PUBLIC AWARENESS OF DEPOSIT INSURANCE AND INVESTOR COMPENSATION SCHEMES IN BULGARIA - Irina Kazandzhieva; Elena Ralinska (Business & Management Compass)
The purpose of deposit insurance and investor compensation schemes is to protect the clients of banks and investment intermediaries by providing compensation in the case of unavailability of clients’ deposits or assets. Generally, knowledge about the activities of both schemes is rather limited by the public. This is observed not only in developing countries, but also in the developed ones. This problem is called public awareness.